Act Incorporating the City of Cincinnati, and the Ordinances of Said City Now in Force, at 44, An Ordinance to prohibit shooting within the bounds of the corporation (1828) - (:unkn) unknown (My University, 1818)
That each and every person who shall shoot , or fire off, any rifle, musket, fowling piece, pistol, or any other fire arms, or discharge squibs, crackers, or any other fire works within the bounds of the Corporation, he or she shall, on conviction thereof before the Mayor forfeit and pay to the said Mayor for the use of the Corporation, for each and every such offence, a sum not less than Two Dollars, nor more than Ten Dollars,
Keywords: DISCHARGE